La contratación pública y su influencia en la ejecución del presupuesto participativo del Gobierno Autónomo Descentralizado Municipal cantón Bolívar, período 2022 - Hidalgo Vera, Linda Karol (2024)
The present study aimed to analyze the influence of public procurement on the execution of the participatory budget of the Municipal Government Autonomous Decentralized (GAD) of the Bolívar canton during the 2022 period. The objective was to understand how public procurement procedures impact the efficiency and transparency of the participatory budget, proposing strategies to strengthen its implementation. The research adopted a mixed methodological approach, combining inductive, deductive, analytical, and synthetic methods to interpret the data and formulate conclusions. It was found that the current legal framework establishes a general framework for public procurement and participatory budgeting; however, the Municipal GAD of the Bolívar canton does not have specific internal regulations to articulate the procurement processes. Additionally, it was identified that the execution of the participatory budget is affected by inefficiency in public procurement procedures, evidenced by budget extensions, modifications to the Annual Procurement Plan, and limited accessibility to information for citizens, generating distrust in the community. For this reason, the conclusions highlight the importance of implementing the action plan as an initiative to improve the management of public resources, promoting efficiency and active community participation in the processes of participatory budgeting.